The potential for dental plaque to protect against erosion using an in vivo‐in vitro model — A pilot study - Cheung, A.; Zid, Z.; Hunt, D.; McIntyre, J. (Australian dental journal, 2005)
Background: Tooth erosion is a problem for professional wine tasters (exogenous erosion from frequent exposure to wine acids) and for people with gastro oesophageal reflux disease (GORD) and bulimia who experience frequent reflux of gastric contents into the mouth (endogenous erosion from mainly HCl). The objective in this study was to determine whether plaque/pellicle could provide teeth with any protection from two common erosive acids, using an in vivo‐in vitro technique. Methods: Tiles of human tooth enamel and root surfaces were prepared from six extracted, unerupted third molar teeth and sterilized. Mandibular stents were prepared for six volunteer subjects and the tiles bonded to the buccal flanges of these stents. They were worn initially for three days to permit a layer of pellicle and plaque to form over the tile surfaces, and for a further 10 days of experimentation. Following cleaning of the plaque/ pellicle layer from the tiles on the right side flange, all the tiles were submerged in either 0.06M HCl or white wine for an accumulated time of 600 and 1500 minutes, respectively. Depths of erosion were determined using light microscopy of sections of the enamel and root tiles. SEM of the lesion surfaces was carried out to investigate the nature of erosive damage and of plaque/pellicle remnants. Results: Retained plaque was found to significantly inhibit dental erosion on enamel, from contact with both HCl and wine, compared with that resulting following its removal. However, it was found to provide no significant protection on root surfaces. SEM analysis of the tile surfaces revealed marked etching of enamel on the cleaned surfaces, and considerable alteration to the appearance of remaining plaque and pellicle on most surfaces. Conclusion: Within the limitations of numbers of specimens, dental plaque/pellicle provided a significant level of protection to tooth enamel against dental erosion from simulated gastric acids and from white wine, using an in vivo‐in vitro model. It was unable to provide any significant protection to root surfaces from these erosive agents. Possible reasons for this difference are explored.